INSTITUTIONAL FINANCIAL RESOURCE DYNAMICS AND TOTAL QUALITY MANAGEMENT ACHIEVEMENT IN TECHNICAL INSTITUTIONS IN KENYA - Macharia, Joseph Mwangi; Chui, Dr. Mary Mugwe; Edabu, Dr. Paul (African Journal of Education and Practice, 2020)
Purpose: Total quality management in has been focal towards industrialization in Kenya. However, financial dynamics has not fully met the management level expected in technical training. The study aimed at evaluating the influence of financial resource dynamics on the achievement of total quality management in public Technical Training Institutions. Objectives were to assess the influence of the financial resource dynamics; influence of performance on the achievement of total quality management. Resource Dynamic and total quality management theories guided the study. Methodology: Mixed methodology research and concurrent triangulation design were used. Target population was 1664 participants: 52 principals, 260 Heads of departments, 1300 lecturers and 52 student leaders. Purposive sampling was conducted on principals and student leaders; random sampling on Heads of Departments and lecturers yielding 499 (30%) participants. Principals, students and lecturers were given questionnaires and interview guide to Heads of Departments. Piloting of instruments was carried out in two institutions at interval of two weeks and a reliability index of 8.0 using Cronbach alpha scale obtained. 350 out of 499 respondents participated in the at a response rate of 70.14%. Qualitative data was analyzed thematically. Statistical Package for Social Sciences version 23.0 was used quantitative data analysis at 95% level of confidence. Findings: The results of the study indicate that, financial resources dynamics positively influences total quality management at 70%. However, negative participation at 48% and allocation at 22%. The study recommends on improvement on allocation and participation of the local community in all Technical Training Institutions in Kenya. Unique Contributions Theory, Practice and Policy: recommends that Ministry of Education should ensure timely allocation of finances to all technical training institutions. TTs should adhere to procurement guidelines of instructional materials